Posted by
**Tammy** on
.

Find the derivative of

a) y=cos (x/2)

b) yx-3x^2 +6 = y^4 + x

a) -sin (x/2)(2+x)/2^2

-sin(x/2)(x/2)

b) x dy/dx + y - 6x = 4y^3 dy/dx + 3x^2

dy/dx (x -4 y^3) = 3x^2 -y +6x

dy/dx = (3x^2 -y +6x)/(x -4 y^3)

I used inplicit differation for part b

are these correct? Thanks for your help in advance!

your first answer makes no sense.

you are simply finding the derivative of

y = cos (1/2)x

which is

y'=-1/2 sin (x/2)

your second equation:

If your last term of the equation was a typo and it was x^3, then you are correct.

I like the way you showed the first line of your implicit derivative, but according to that line the last term must have been x^3 instead of x.